European Union Competition Policy versus Industrial Competitiveness Stringent Regulation and its External Implications - Yoshizawa, Hikaru (Globalisation, Europe, and Multilateralism, 2022)
The book examines whether EU competition policy is applied fairly and consistently to EU and non-EU firms despite persistent political pressure from member states for a relaxation of the rules and deals with the dilemma of regional organisations in the global political economy. Focussing on the EU's desire to achieve balance between the promotion of market competition and the enhancement of international competitiveness, the book explores the validity of its attempts successfully to ensure a 'stringent competition policy' which is nationality-blind and comparatively strict. Finally, it shows that the competition-competitiveness dilemma remains unresolved because the EU's capability to set global regulatory standards is constrained by competition and the need to engage in multilateral forums, such as the WTO and the International Competition Network. This book will be of key interest to scholars and students of European Union studies, EU competition law and policy, EU external action and more broadly to global governance, international political economy and international relations.